A Novel Duplication in ATXN2 as Modifier for Spinocerebellar Ataxia 3 (SCA3) and C9ORF72‐ALS. Issue 2 (15th October 2020) - Laffita‐Mesa, Jose Miguel; Nennesmo, Inger; Paucar, Martin; Svenningsson, Per
Abstract: Background: The ataxin‐2 ( ATXN2 ) gene contains a cytosine‐adenine‐guanine repeat sequence ranging from 13 to 31 repeats, but when surpassing certain thresholds causes neurodegeneration. Genetic alterations in ATXN2 other than pathological cytosine adenine guanine (CAG) repeats are unknown. Methods/Results: We have identified a 9–base pair duplication in the 2‐gene ATXN2 sense/antisense region. The duplication was found in a Swedish family with spinocerebellar ataxia 3 with parkinsonism, conferring a deviated age at onset unexplained by the concomitant presence of ATXN2 intermediate alleles. Similarly, C9ORF72 amyotrophic lateral sclerosis cases bearing the same duplication had earlier age at onset than those with C9ORF72 and ATXN2 intermediate alleles. No effect was evident in Parkinson's disease (PD) cases without known PD gene mutations. Conclusions: We describe the first genetic alteration other than the known intermediate‐range CAG repeats in ATXN2 . This 9–base pair duplication may act as an additional hit among carriers of pathological nucleotide expansions in ATXN3 and C9ORF72 with ATXN2 intermediate. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.